Nanoscale insights into Pt-impregnated mixtures of zeolites. Issue 32 (27th July 2017) - Mendes, Pedro S. F.; Taleb, Anne-Lise; Gay, Anne-Sophie; Daudin, Antoine; Bouchy, Christophe; Silva, João M.; Ribeiro, M. Filipa
Abstract : The study of catalysts prepared by Pt deposition over mixtures of HUSY and HBEA zeolites revealed a selective deposition of Pt in HBEA sample. The characterization of nanoscale properties, as illustrated, was crucial to fully elucidate the structure of the bifunctional catalysts. Abstract : A series of catalysts prepared by Pt deposition over intimate mixtures of HUSY and HBEA zeolites was investigated for the first time and compared to individual Pt/zeolite solids. The samples were characterized through macroscopic techniques and at the nanoscale by electron microscopy and electron tomography, in order to evaluate both the acid and the hydrogenation functions. Comparable macroscopic properties were observed between Pt-impregnated individuals and zeolite mixtures. In contrast, at the nanoscale, differences were evident. When mixtures of zeolites were impregnated, Pt was not homogeneously distributed over the sample. In fact, Pt was located mainly on the HBEA zeolite rather than on HUSY, as confirmed by TEM-EDS semi-quantification. This selectivity in Pt location was tentatively explained by the higher amount of terminal silanol and EFAL species in the HBEA sample. The preferential Pt location at the nanoscale may open up new possibilities in the design and application of hybrid catalysts.